Achieving nitritation by treating sludge with free nitrous acid: The effect of starvation. (January 2019) - Nan, Xi; Ma, Bin; Qian, Wenting; Zhu, Hongbo; Li, Xiyao; Zhang, Qiong; Peng, Yongzhen
Graphical abstract: Highlights: The sludge treatment with FNA is a novel strategy to achieve nitritation. Pre-starvation enhanced the resistance of sludge to FNA. This led to a decrease in nitrite accumulation rate (NAR). The post-starvation also decreased NAR. Both pre-starvation and post-starvation should be avoided to ensure a high NAR. Abstract: Side-stream sludge treatment using free nitrous acid (FNA) is a novel strategy to achieve nitritation in mainstream of wastewater treatment plants (WWTPs). To optimize nitritation, the effect of starvation on this strategy was investigated in this study. The results showed that pre-starvation, which is the starvation before FNA treatment, enhanced the resistance of sludge to FNA. This led to a decrease in the nitrite accumulation rate (NAR), which dropped from 70% to 27% after aerobic pre-starvation. This was further confirmed in the FNA treatment using the sludge collected from the secondary settling tank (anoxic pre-starvation) and the aerobic zone (without starvation) of an Anaerobic-Anoxic-Oxic system. The post-starvation, which was the starvation after FNA treatment, decreased NAR from 63% to 14%. To obtain a higher NAR, the sludge used for FNA treatment should be collected from aerobic zone, and be returned to aerobic zone after treatment to avoid pre-starvation and post-starvation.